Biological Therapy in Pediatric Inflammatory Bowel Disease: A Systematic Review. Issue 2 (February 2017) - Corica, Domenico; Romano, Claudio
Abstract : The incidence of inflammatory bowel disease (IBD) has increased steadily worldwide, both in adult and in children; approximately 25% of IBD patients are diagnosed before the age of 18. The natural history of IBD is usually more severe in children than in adults, and can be associated with linear growth impairment, delayed puberty onset, reduced bone mass index, malnutrition, and the need for surgery. Biological therapies, especially blocking tumor necrosis factor-α (TNFα), have radically modified the treatment strategies and disease course of IBD in children. In particular, drugs such as Infliximab and Adalimumab are routinely used in the treatment of pediatric IBD. The role of Infliximab and Adalimumab in the management of pediatric IBD has been recently updated in the Consensus guidelines of ECCO/ESPGHAN. Data regarding short-term and long-term efficacy and safety of these drugs in children, and the effects of "top-down" and "step-up" strategies, are lacking. In this paper, the authors will review current indications, efficacy, and safety of biological therapy in pediatric IBD patients, evaluating all articles published after ECCO/ESPGHAN guidelines publication. The authors carried out a systematic search through MEDLINE through PubMed (http://www.ncbi.nlm.nih.gov/pubmed/ ) Embase, CINAHL, Cochrane Library, and gray literature, from January 2013 to January 2016. Anti-TNFα has been shown to be effective and safe to maintain remission and to achieve mucosal healing. Multicenter trials based on large sample size cohorts are needed to better clarify long-term efficacy of anti-TNFα and the real incidence of treatment-related complications in pediatric IBD.